Trends, Clinical Profiles, and Demographics of Psychiatry Referrals: A Retrospective Record-based Study with Insights into Age-related Trends - Yogender Kumar Malik; Adwitiya Ray; Anwesha Chatterjee; Sujata Sethi (International Journal of Advanced Medical and Health Research)
Background: The intricate bidirectional relationship between physical and psychological health is well established. Studies highlight a significant prevalence of diagnosable psychological comorbidities in patients with physical disorders, often impacting health outcomes. Consultation-liaison psychiatry (CLP) specializes in integrating psychiatric care into general hospitals, addressing the intersection of physical and mental health. Despite its pivotal role, CLP referral rates in most parts of the world remain low, with few institutions offering specialized CLP services. Furthermore, research in this field is scarce. Hence, this study aimed to assess the 3-year trend in the pattern and utility of CLP services in a tertiary care center in North India. Methods: This is a retrospective, descriptive study of 3-year referral records maintained by the CLP services in a multispecialty tertiary care teaching hospital. Results: The mean age of the sample was 36.0 ± 16.4 years, with predominant referrals from medicine (51.4%) and surgery (15.8%) departments. Psychiatric diagnoses included depression, delirium, psychosis, mania, anxiety, eating disorder, and dissociation. Geriatric patients had the highest prevalence of delirium (24.1%), whereas intentional self-harm was often seen in adults (13.6%); alcohol dependence was observed across all age groups. More than a quarter (26.6%) had no specific psychiatric diagnosis. Interventions varied, with psychotropic medications being the most common treatment in adults (58%) while psychotherapy was primarily used in children (39.5%). Conclusion: This study highlights an increasing trend in CLP referrals, with predominant cases from medicine and surgery departments. The high prevalence of delirium among older adults and self-harm among adults underscores the need for better integration of mental health services in general hospitals.